Implementasi Program Beasiswa Full Sarjana di Kota Cilegon - Sheila Sabina Putri Defa; Titi Stiawati; Sierfi Rahayu (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This research was motivated by the low Gross Higher Education Participation Rate (APKPT) and low Labor Force Participation in Cilegon City. The government has issued a Higher Education Scholarship Program, namely a Full Undergraduate Scholarship so that the people of Cilegon City can meet the minimum industrial needs in Cilegon City. The aim of this research is to find out whether the implementation process for the Full Undergraduate Scholarship program is optimal, in terms of several problems related to the annual target of scholarship recipients not having reached the target, lack of socialization, incompatibility with scholarship registration requirements, and the flow of registration for full undergraduate scholarship candidates. This study uses a qualitative method. Data was collected by interviews with 15 informants consisting of implementing agents, scholarship recipients and the community. Data were reduced according to the theory of Donald S. Van Meter and Carl E. Van Horn (1975) with 6 aspects, namely; (1) policy size and objectives; (2) resources; (3) characteristics of implementing agents; (4) the attitude or tendency of the implementer; (5) communication between organizations; (6) Economic, Social and Political Environment. The results of the research show that there is a misunderstanding of communication between organizations and the community which causes a lack of information regarding full undergraduate scholarships, the education office only sets a Certificate of Incompetence as a requirement, and all prospective recipients register in the same way, namely through the Sicerdas application, but in the first year it is not use the Sicerdas application for scholarship registration.